2020
DOI: 10.1371/journal.pone.0237085
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal sepsis at Mulago national referral hospital in Uganda: Etiology, antimicrobial resistance, associated factors and case fatality risk

Abstract: Background Sepsis is the third most common cause of death among neonates, with about 225,000 newborns dying every year globally. Data concerning the microbial etiology of neonatal sepsis and antimicrobial resistance profiles of its causative agents are necessary to inform targeted and effective treatment and prevention strategies. Objective To determine the proportion of newborns with symptoms and signs of sepsis who had a positive blood culture, its bacterial etiology, the antimicrobial resistance patterns as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
31
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 45 publications
12
31
8
Order By: Relevance
“…The resistance profiles observed in this study were largely similar to those described elsewhere in Uganda. Nevertheless, the largest discrepancies between this and other studies were the universal susceptibility to clindamycin at FPRRH, whilst a relatively high 41% resistance was found at Mulago, and for trimethoprim (43% in this study, and ≥89% in Mulago), and chloramphenicol, for which although rates of resistance vary between 14% - 88% elsewhere [9, 13, 14, 46, 50], FPRRH strains were almost all susceptible. National advice on control strategy based on national clinical guidelines, or data that may be focused upon major urban centres, are not always aligned with antibiotic susceptibility observed at the local level, emphasising the requirement for local knowledge such as that described here [16].…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…The resistance profiles observed in this study were largely similar to those described elsewhere in Uganda. Nevertheless, the largest discrepancies between this and other studies were the universal susceptibility to clindamycin at FPRRH, whilst a relatively high 41% resistance was found at Mulago, and for trimethoprim (43% in this study, and ≥89% in Mulago), and chloramphenicol, for which although rates of resistance vary between 14% - 88% elsewhere [9, 13, 14, 46, 50], FPRRH strains were almost all susceptible. National advice on control strategy based on national clinical guidelines, or data that may be focused upon major urban centres, are not always aligned with antibiotic susceptibility observed at the local level, emphasising the requirement for local knowledge such as that described here [16].…”
Section: Discussioncontrasting
confidence: 89%
“…AST suggested that 71% of isolates (29/41) were susceptible to erythromycin and these phenotypes matched the genotype in most cases (26/29). Thirteen isolates (32%) were found to be resistant to erythromycin, which is considerably lower than reported by several other Ugandan studies [35, 46, 49, 50] and all erythromycin-resistant isolates were susceptible to clindamycin. For some isolates, this could be explained by the presence of an inducible efflux pump gene ( msrA ), which is implicated in resistance to erythromycin [51].…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…AST suggested that 71 % of isolates (29 of 41) were susceptible to erythromycin and these phenotypes matched the genotype in most cases (26 of 29). Thirteen isolates (32 %) were found to be resistant to erythromycin, which is considerably lower than reported by several other Ugandan studies [35,47,50,51] and all erythromycin-resistant isolates were susceptible to clindamycin. For some isolates, this could be explained by the presence of an inducible efflux pump gene (msrA), which is implicated in resistance to erythromycin [52].…”
Section: Genomic Correlation With Phenotypic Amr Profilescontrasting
confidence: 58%
“…SVD was also associated with neonatal septicaemia, here babies could have been exposed to maternal vaginal and fecal bacteria [46]. which was contrary to other studies that showed cesarean section was more associated with culture-positive cases [47]. This justi es the need for infection control practices and improving mother hygiene as reported by Ahmed [48].…”
Section: Discussionmentioning
confidence: 91%